Cell adhesion evaluation of laser-sintered HAp and 45S5 bioactive glass coatings on micro-textured zirconia surfaces using MC3T3-E1 osteoblast-like cells - Mesquita-Guimarães, J. (2020)
Laser texturing is a technique that has been increasingly explored for the surface modification of several materials on different applications. Laser texturing can be combined with conventional coating techniques to functionalize surfaces with bioactive properties, stimulating cell differentiation and adhesion. This study focuses on the cell adhesion of laser-sintered coatings of hydroxyapatite (HAp) and 45S5 bioactive glass (45S5 BG) on zirconia textured surfaces using MC3T3-E1 cells. For this purpose, zirconia surfaces were micro-textured via laser and then coated with HAp and 45S5 BG glass via dip coating. Afterwards, the bioactive coatings were laser sintered, and a reference group of samples was conventionally sintering. The cell adhesion characterisation was achieved by cell viability performing live/dead analysis using fluorescence stains and by SEM observations for a qualitative analysis of cell adhesion. The in vitro results showed that a squared textured pattern with 100μm width grooves functionalized with a bioactive coating presented an increase of 90% of cell viability compared to flat surfaces after 48h of incubation. The functionalized laser sintered coatings do not present significant differences in cell viability when compared to conventionally sintered coatings. Therefore, the results reveal that laser sintering of HAp and 45S5 BG coatings is a fast and attractive coating technique.